Revision of the cranaid genera Phalangodus, Iquitosa and Aguaytiella (Opiliones: Laniatores: Gonyleptoidea) - Hara, Marcos Ryotaro; Pinto-Da-Rocha, Ricardo; Villarreal M., Osvaldo (Zootaxa, 2014)
The monotypic genus Temucus Roewer, 1943, originally placed in Pachylinae (Gonyleptidae) is transferred to the Cranainae (Cranaidae) and synonymized with Phalangodus Gervais, 1842, therefore Phalangodus palpiconus (Roewer, 1943) comb. nov. is proposed. The synonymy is based on the following features: (i) the outline of dorsal scutum type alpha; (ii) the thickened pedipalpal claw in males; (iii) pedipalpal femur with a few ventral enlarged tubercles restricted to the median ventral region, and a conspicuous group of very large and acuminated tubercles basally; (iv) ventral plate of penis with a rather elevated number of cylindrical, straight and sharp distal pairs of setae and a notorious reduction in the number of the basal pairs of setae; (v) penis stylus straight, its distal tip rounded in a mushroom-like shape without stylar caps. The record of P. palpiconus to Chile is doubtful. We also propose the revalidation of Iquitosa Roewer, 1943, hitherto considered a junior synonym of Phalangodus. Iquitosa is revised and the male of its type species, I. poecilis, is reported for the first time. Aguaytiella Goodnight & Goodnight, 1943, a monotypic genus which superficially resembles Iquitosa is also revised. In this article, we report data of male genitalia of Iquitosa and Aguaytiella, providing redescriptions and diagnoses of those genera and species, and a discussion of their relationship with other cranaids.